Diagnostic workup in children with arthrogryposis: description of practices from a single reference centre, comparison with literature and suggestion of recommendations. Issue 1 (7th December 2021) - Le Tanno, Pauline; Latypova, Xenia; Rendu, John; Fauré, Julien; Bourg, Véronique; Gauthier, Marjolaine; Billy-Lopez, Gipsy; Jouk, Pierre-Simon; Dieterich, Klaus
Abstract : Introduction: Arthrogryposis multiplex congenita (AMC) refers to a clinical presentation of congenital contractures involving two or more body areas. More than 400 distinct conditions may lead to AMC, making the aetiological diagnosis challenging. The objective of this work was to set up evidence-based recommendations for the diagnosis of AMC by taking advantage of both data from our nation-wide cohort of children with AMC and from the literature. Material and methods: We conducted a retrospective single-centre observational study. Patients had been evaluated at least once at a paediatric age in the AMC clinic of Grenoble University Hospital between 2007 and 2019. After gathering data about their diagnostic procedure, a literature review was performed for each paraclinical investigation to discuss their relevance. Results: One hundred and twenty-five patients were included, 43% had Amyoplasia, 27% had distal arthrogryposis and 30% had other forms. A definitive aetiological diagnosis was available for 66% of cases. We recommend a two-time diagnostic process: first, non-invasive investigations that aim at classifying patients into one of the three groups, and second, selected investigations targeting a subset of patients. Conclusion: The aetiological management for patients with AMC remains arduous. This process will be facilitated by the increasing use of next-generation sequencing combined with detailed phenotyping. Invasive investigations should be avoided because of their limited yield.